Modified Blalock-Taussig Shunt and Levosimendan for Left Ventricular Preparation in a Child with Transposition of Great Arteries and Regressed Ventricle Undergoing Rapid 2 Stage Arterial Switch Operation - Sahu, Manoj Kumar (Ann Card Anaesth, 2017)
Rapid two-stage arterial switch operation (ASO) is very relevant as many patients of transposition of great arteries (TGA) present late to the hospital when primary switch either is not possible or carries a high risk of morbidity and mortality. Hence, other means apart from the traditional methods of left ventricle preparedness should be tried to help this category of patients, who are to undergo rapid two-stage ASO. We successfully used levosimendan and continuous positive airway pressure after 1(st) stage operation in a patient with dTGA and regressed ventricle, which helped in left ventricular preparedness, and the child underwent rapid two-stage ASO uneventfully.